Management of intratonsillar abscess in children. Issue 4 (5th August 2013) - Ulualp, Seckin O.; Koral, Korgun; Margraf, Linda; Deskin, Ronald
Abstract: Background: The aim of this study was to assess outcomes of medical and surgical treatment of intratonsillar abscess in children. Methods: The medical charts of children with intratonsillar abscess were reviewed to obtain information on history and physical examination, imaging, management, and follow‐up assessment. Results: Eleven children (six male, five female; age range, 4–18 years) were identified. The common complaints included sore throat, fever, and odynophagia. Asymmetric tonsil hypertrophy was present in nine patients and erythema of tonsils in all patients. Peritonsillar fullness was present in three patients. One patient needed emergency intubation due to respiratory compromise. Computed tomography indicated unilateral intratonsillar abscess in nine patients, bilateral intratonsillar abscess in one, and unilateral phlegmon in one. Inflammatory changes were observed in the parapharyngeal space in all patients, retropharyngeal space in one, and pyriform sinus and aryepiglottic folds in two. Antibiotic treatment included clindamycin in seven patients, ampicillin/sulbactam in one, and clindamycin plus ceftriaxone in three. The patients with respiratory compromise underwent surgery prior to antibiotic treatment. Patients with isolated intratonsillar abscess or phlegmon had resolution of their symptoms with i.v. antibiotic treatment. Patients with combination of intratonsillar and peritonsillar abscess required incision and drainage of peritonsillar abscess. Conclusions: Clinically stable children with intratonsillar abscess or phlegmon respond to i.v. antibiotic therapy. Surgical drainage can accomplish clinical resolution in the presence of a combination of intra‐ and peri‐tonsillar abscess, airway compromise, or unresponsiveness to medical treatment.